A Professional Development Program in Management of Midwifery Emergencies for Midwifery Graduates - Soheila Mohamadirizi; Ashraf Kazemi; Fariba Haghani; Mojgan Janighorban (Wolters Kluwer Medknow Publications, 2024)
Background: Midwifery emergencies can be managed by providing effective and quality care through a skilled workforce. Improving the quality of midwifery care requires the professional development of midwives, especially those who are novice, to maintain their capabilities and enhance their performance. This study was designed to develop a professional development program in the management of midwifery emergencies for midwifery graduates. Materials and Methods: This mixed-method study was conducted in two phases. In the first phase, a qualitative study was conducted to investigate the program needs, facilitators, and barriers to the management of midwifery emergencies in midwifery graduates. Further, the initial version of the program was developed based on the results of the qualitative study and literature review. The Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model was used to develop a professional development program for the management of midwifery emergencies. The developed program was then evaluated and approved by a panel of experts. In the second phase, the developed professional development program is implemented, and its impacts are evaluated. Finally, the final professional development program in the management of midwifery emergencies for midwifery graduates is provided. Results: In total, 2,360 primary codes were extracted and merged into 210 codes. After extracting the sub-categories and categories, a review of the texts was conducted, and the final program was developed. Conclusions: Using a professional development program for newly graduated midwives is an effort to improve the health of mothers and infants who receive these services.